Management of Hypertension: JNC 8 and Beyond - Ezra A. Amsterdam; Sandhya Venugopal; Jonathan Bui; Balasingam Thevakumar; Angela Thinda; Sabrina Virk; William J. Bommer; Aman Khullar; Gagan Singh (Cardiovascular Innovations and Applications, 2016)
Hypertension is a leading risk factor for cardiovascular disease, the leading cause of death and morbidity in our society and on a global scale. Major components of cardiovascular disease include stroke, coronary artery disease, heart failure, and chronic kidney disease, in all of which hypertension plays a major role. The risk of these complications increases directly and linearly with systolic blood pressure starting at 115 mmHg. Although usually asymptomatic, hypertension is readily detectable on physical examination and is amenable to both lifestyle modification and pharmacologic treatment in most patients. However, large proportions of the hypertensive population remain undetected and undertreated. Numerous guidelines have been issued during the past few decades to promote detection and optimal therapy. Despite the increase in risk with systolic blood pressure greater than 115 mmHg, the generally accepted threshold for diagnosis and treatment has been systolic blood pressure greater than 139 mmHg and diastolic blood pressure greater than 80 mmHg because until recently treatment to lower levels has been associated with an unfavorable relation between clinical benefit and harm. In the past several years, new guidelines, advisories, commentaries, and clinical trials have provided evidence for a potential change in current recommendations for the management of hypertension. In this regard, the long-awaited eighth report of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure recommended patients older than 60 years be treated to a systolic blood pressure of less than 150 mmHg, which has generated considerable controversy and caution. The striking findings of the Systolic Blood Pressure Intervention Trial (SPRINT) have received considerable attention because of the demonstration that intensive therapy to a target systolic blood pressure below 120 mmHg decreases cardiovascular mortality and morbidity more than less intensive treatment to a target systolic blood pressure below 140 mmHg, but this approach is not fully generalizable because the trial excluded patients younger than 50 years and those with diabetes and prior stroke. This article addresses major issues in the management of hypertension, including those in the seventh and eight reports of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure and subsequent studies, considering maintenance of prior standards as well as the potential application of important new findings.